Remotely Almost Periodic Solutions of Ordinary Differential Equations. (18th May 2021) - Maulén, C.; Castillo, S.; Kostić, M.; Pinto, M.
Abstract : In this paper, we analyze the existence and uniqueness of remotely almost periodic solutions for systems of ordinary differential equations. The existence and uniqueness of remotely almost periodic solutions are achieved by using the results about the exponential dichotomy and the Bi-almost remotely almost periodicity of the homogeneous part of the corresponding systems of ordinary differential equations under our consideration.